Service-learning in United States higher education = Học tập công ích tại các trường đại học Hoa Kỳ - Nguyễn, Lê Hường (2020)
The use of service-learning has been increasingly encouraged across American higher education as a popular teaching and learning approach in providing opportunities for students to connect in a meaningful way with the outside world and tie knowledge acquired from books to real life settings. Few pedagogical innovations have attained success in such a short period of time as service-learning has. The purpose of this study is to question and report findings for four key questions: What types of service-learning activities are there? What are the historical and philosophical roots of service-learning? What elements are used to measure the successfulness of service-learning programs? What are the impacts of service-learning on participating students? For the purpose of this study, the data were collected through comparing and contrasting different related documents such as websites, books, journals, and articles. Results show various benefits American students gain from participating in service-learning including academic, civic, and personal benefits. The success of service-learning programs was clearly shown through the simultaneous renewal of the five major components: vision and leadership; curriculum and assessment; community and school partnerships; professional development; and continuous improvement. Besides, investigation into the field revealed the forms of service-learning activities which are direct service, indirect service, and advocacy. This paper highlights the most important events in service-learning history and analyzes the philosophical roots integrated in service learning. Finally, implications are discussed for Vietnamese administrator and educators to employ this innovative pedagogical tool.